Water pollution in Kucukcekmece Lake, Istanbul, Turkey - Pehlivan, Rustem (Journal of Nepal Geological Society, 2000)
Water samples collected in February and August 1997 from the Kucukcekmece Lake were analysed by ICPMS-200 to determine the heavy metal concentration s (i.e., Hg, Cd, Pb, As, Cu, Cr, Co, Ni, Zn, Fe, Mn, Se, Ba, Al, and U). A comparison of these data with those of 1985, 1989, and 1995 revealed Hg and U contamination in the northern region, whereas Pb, Cu and Se contamination in the southern region of the Kucukcekmece Lake. Beside s, the influent waters were collected from the respective stream mouths, and were also analysed for heavy metal concentrations. The results showed the following contaminants: Hg, Se and U in the Ispartakule Stream, Hg, Cu and Se in the Sazli Stream, and Cu, Se and U in the Nakka Stream. On the other hand, a comparison of the results of February 1997 with those of August 1997 revealed that the amounts of As, Cu, Cr, Mn, Ba and Fe had decreased, but those of Pb, Ni, Zn and Se had increased in the lake since February 1997. Such kind of seasonal variation in concentration of heavy metals is attributed to pollution of the lake water by domestic waste, industrial effluents, and water-rock interactions.